2011
DOI: 10.1002/nme.3156
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of strain smoothing for quadratic and enriched finite element approximations (XFEM/GFEM/PUFEM)

Abstract: To date, the SFEM has only been investigated for bilinear and Wachspress approximations and is limited to linear reproducing conditions. The goal of this paper is to extend the strain smoothing to higher order elements and to investigate numerically in which condition strain smoothing is beneficial to accuracy and convergence of enriched finite element approximations. We focus on three widely used enrichment schemes, namely: (a) weak discontinuities; (b) strong discontinuities; (c) near-tip linear elastic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 48 publications
1
108
0
Order By: Relevance
“…From the numerical study presented, it was concluded that the CS-FEM technique is robust, computationally inexpensive, free of locking and importantly insensitive to mesh distortions. In [2], CS-FEM has been combined with the extended FEM to study moving boundary problems.…”
Section: Introductionmentioning
confidence: 99%
“…From the numerical study presented, it was concluded that the CS-FEM technique is robust, computationally inexpensive, free of locking and importantly insensitive to mesh distortions. In [2], CS-FEM has been combined with the extended FEM to study moving boundary problems.…”
Section: Introductionmentioning
confidence: 99%
“…SFEMs using quadratic 8-node quadrilateral elements (Q8) does not pass the patch test [32]. Further investigation by authors showed the same shortcoming for quadratic 6-node triangular elements.…”
Section: Different Coupled Hydro-mechanical Sfem Modelsmentioning
confidence: 99%
“…where is the standard deviation of the th variable, is the arbitrary factor, and the initial value range is (1,3). The computational formula is as follows:…”
Section: Sampling Of Classical Rsmmentioning
confidence: 99%